Self-rated health of the older adults in the northeastern region of India: Extent and determinants - Rupon Basumatary; Simi Kalita; Himakshi Bharadwaj (Clinical Epidemiology and Global Health)
Aim: To analyse older adults’ self-rated health (SRH) in the northeastern region (NER) of India. Methods: This study uses data from the 75th round survey on Household Social Consumption: Health conducted by the National Statistical Office (NSO), India, during July 2017–June 2018. The sample for the present consists of 3988 persons aged 60 years and above. Binary logistic regression procedure has been used to identify the determinants of SRH of the older adults. Results: More than three-fourth of the older adults in the region perceive their health as ‘good’ or ‘very good’. Older adults' SRH varies with their demographic and socioeconomic profiles. Conclusion: In the context of the NER, creating employment opportunities for the older adults may be of policy importance in the light of the fact that the majority of them report good or very good health but remain dependent on others financially – partially or fully. Achieving ‘healthy ageing’, as defined by WHO, nevertheless requires measures that goes beyond financial independence of the older adults to support their mental health and social wellbeing as well. Future studies may focus on older adults' objective health, health risks protection and their labor market participation in the region.